A study on standard procedure and employee satisfaction factor towards the level of effectiveness in conducting performance appraisal based on employees perception at registrar's office, Universiti Malaysia Kelantan (UMK) / Suzilawati Hussin - Hussin, Suzilawati (Faculty of Business and Management, 2018)
The aim of this research was to study the standard procedure and employee satisfaction toward the level of effectiveness of performance appraisal based on employee perception at Registrar's Office, Universiti Malaysia Kelantan (UMK). In this correlational research, there are two objectives research and two research questions were designed to conduct this study. Other than that, questionnaires were used as a tool to collect data and then analysed using the statistical package for social science (SPSS). The correlation analysis results in this study show that there is strong or positive relationship between employee's satisfaction factor and standard procedure factor toward the level effectiveness of performance appraisal based on employee's perception. Thus, the result of descriptive finding based on the employee's perception showed that most factors influence the effectiveness level of performance appraisal is employee's satisfaction rather than the standard procedure. In addition, there a few recommended should implement at the Registrar's Office, UMK to increase the performance appraisal process such as put in the practice the procedure of performance appraisal, provide proper training, conducting the plan to increase employees career and the self-development and regularly communicate about the value of performance appraisal.